Climate Protection and Development - Ackerman, Frank; Kozul-Wright, Richard; Vos, Rob (The United Nations Series on Development, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on bloomsburycollections.com. Writing about climate change often falls into one of two opposite traps - predicting either calamity or apathy - both of which this book avoids. This is not a story of gloom and doom, of inevitable climate catastrophe. On the contrary, this book spells out, in more detail than usual, what can and should be done to avert the real risks of disaster. Nor is it one of complacent congratulation for "win-win" initiatives, cautiously incremental steps, and "green" consumer choices.Climate Protection and Development summons us to an endeavour worthy of the resources and ingenuity of the twenty-first century - towards bold initiatives with big costs, and much bigger benefits. This book explores the interconnected issues of climate and development, laying the groundwork for just such a new deal. It presents a challenging agenda, and highlights the needs and perspectives of developing countries which may be unfamiliar or uncomfortable to readers in high-income countries. The unfortunate truth is that any large country, or group of mid-sized countries, can veto any global climate solution by refusing to participate, so a solution will only work if it works for everyone.